Development of Monzer Kahf’s Islamic Consumption Theory and Ethics - Bella, Alif Mujiyana Eka (Sharia Faculty Islamic Economic Law Study Department, 2024)
Monzer Kahf as a contemporary Muslim intellectual, has successfully articulated the concepts of welfare, utility, and consumption optimization for Muslim individuals. In the context of Islamic consumption theory, Monzer Kahf introduced the concept of rationality, while in Islamic consumption ethics, Kahf introduced the concept of 'Final spending'. The purpose of this study is to design a theoretical framework and Islamic consumption ethics, which is expected to be the main foundation for Muslims' understanding of the essence of consumption activities, with reference to Monzer Kahf's economic thought. The methodology used is a qualitative method using library research. The result of this research is that Monzer Kahf's economic thought provides a strong foundation for building a model of construction of Islamic consumption theory and ethics that can be a guide for individuals and society. By building this construction of Islamic consumption theory and ethics, it is hoped that people can adopt consumption practices that are in accordance with Islamic values, live a sustainable economic life, and help create a more just and empowered society.